1993
DOI: 10.1021/ar00027a007
|View full text |Cite
|
Sign up to set email alerts
|

Chiral methyl groups: small is beautiful

Abstract: Chemists, particularly those of the organic or biochemical persuasion, tend to be preoccupied with large molecules and complex structures, not with small and simple compounds. Yet, despite this general mindset, chiral (stereogenic) methyl groups, the smallest asymmetric objects ever synthesized, have for some reason managed to capture our imagination. Ever since the initial disclosure1•2 of methods to synthesize the enantiomers of a methyl group carrying one atom each of , 2H, and 3H and to distinguish the R f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0
2

Year Published

1998
1998
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(34 citation statements)
references
References 52 publications
2
30
0
2
Order By: Relevance
“…The preparation of asymmetric methyl groups has al ong and rich history in organic chemistry [101][102][103][104] with recently identified applicationsi nf undamentalp hysics for measuring parity-violating energyd ifferences between enanteomers. [105] Theu se of ac hiral methyl group CHDT in MOR could lead to chiral molecules that can be directly laser cooled:SrOCHDT and CaOCHDT.…”
Section: Laser-cooled Chiral Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…The preparation of asymmetric methyl groups has al ong and rich history in organic chemistry [101][102][103][104] with recently identified applicationsi nf undamentalp hysics for measuring parity-violating energyd ifferences between enanteomers. [105] Theu se of ac hiral methyl group CHDT in MOR could lead to chiral molecules that can be directly laser cooled:SrOCHDT and CaOCHDT.…”
Section: Laser-cooled Chiral Speciesmentioning
confidence: 99%
“…However,o ur proposed optical cycling schemed elivering $10 3 scattered photons per molecule opens ap ath towards the use of coherent opticalb ichromatic forces (BCF) for rapid deceleration of MOR originating from aC BGB to near the capture velocity of am olecular MOT, v cap $10 ms À1 . [101] Following successful experimental resultsf or atomic beams, there has been different new schemes proposed forefficient laser slowing of diatomic molecules on both electronic [111][112][113] and vibrational transitions. [114] While we surmise that these techniques could be applied to MOR species, detaileds imulations of the bichromatic force in complex multilevel systems (e.g.…”
Section: Coherent Slowingmentioning
confidence: 99%
“…The stereochemical course of side chain attachment was shown to be inversion through the incorporation of methionine stereospecifically deuterated at C-4 (13). This configurational outcome parallels the stereochemistry of addition of the 3-aminopropyl moiety derived from decarboxylated S-adenosylmethionine (AdoMet) 1 operative in the biosynthesis of the polyamines (14 -16), as well as more conventional methyltransferases (17,18), suggesting a role for AdoMet in nocardicin A biosynthesis in vivo. This postulate was borne out in preliminary cell-free studies in which an efficient, time-dependent conversion from nocardicin E (5) to nocardicin A in the presence of AdoMet was demonstrated (19).…”
mentioning
confidence: 82%
“…The chirality of the methyl group was then determined by the enzymatic methods of Arigoni [101] and Cornforth [102]. Hence, it was found that the majority (if not all) of AdoMet-dependent MTases catalyze methyl group transfer with an inversion of configuration which is consistent with a single transfer step and an S N 2-type transition state [103].…”
Section: The Biosynthesis and Metabolism Of Adometmentioning
confidence: 99%